PENEGAKAN HUKUM TERHADAP PELANGGARAN PENAMBANGAN ILEGAL GAS BUMI DI INDONESIA - trio saputra; Suryani Suryani (Jurnal Administrasi Publik dan Bisnis, 2023)
The author conducted this research with the aim of analyzing illegal mining law enforcement in Indonesia. The method used in this study is bilbliometric which is used to communicate the development of a scientific discipline for further research needs. This study aims to hide research developments related to mining from 2017-2022. Research results Illegal mining is one of the problems that is currently still a challenge for the government. Filtering articles using the keywords "illegal mining" and "illegal mining". From a journal that must be indexed by Sinta and Scopus. The results of this study show that of the 200 articles collected, there are 46 articles that are Sinta indexed and 2 Scopus indexed articles.